Seasonal variations in Home Range Size of Capped Langur (Trachypithecus pileatus) in a degraded habitat in Assam, India - Borah, Dhiraj Kumar; Solanki, GhanShyam; Bhattacharjee, Parimal Ch. (Ecological Questions, 2022)
A group of capped langurs, Trachypithecus pileatus comprising eight individuals was studied in Sri Surya Pahar, a degraded habitat in Goalpara district of Assam to record the seasonal variations in distance travelled, home range, and habitat utilization through direct observation supplemented by Geographical Information system (GIS). Scan sampling method was followed to record data on ranging behaviour. Seasonality in the home range size was evident and significant (P<0.01), it was 20 ha in winter, 17 ha in pre-monsoon, 17.75 ha in monsoon and 16.25 ha in retreating monsoon. The mean daily travel distance varied significantly (P<0.01), it was 375 m in retreating monsoon to 490 m in winter. The mean daily travel length was 439 m and the total annual home range size was 38.25 ha. The variation of home range size was correlated with the distribution and abundance of food resources. Home range size and daily travel distance showed significant seasonal variations. In both the cases the ranging patterns were longer during the winter season. This may be due to shortage of new leaves during winter, which is the preferred food item of capped langur. Spatial availability of the different food resources over different seasons may also be a reason for significant changes in ranging pattern during different seasons. The present data on home range size and ranging pattern of capped langur in degraded habitat could be useful for improvement of habitat and the conservation of this endangered species in Assam.